Towards a comprehensive view of the herpes B virus - Lu, Jiangling; Long, Yiru; Sun, Jianhua; Gong, Likun (Frontiers in Immunology, 2023)
Herpes B virus is a biosafety level 4 pathogen and widespread in its natural host species, macaques. Although most infected monkeys show asymptomatic or mild symptoms, human infections with this virus can cause serious neurological symptoms or fatal encephalomyelitis with a high mortality rate. Herpes B virus can be latent in the sensory ganglia of monkeys and humans, often leading to missed diagnoses. Furthermore, the herpes B virus has extensive antigen crossover with HSV, SA8, and HVP-2, causing false-positive results frequently. Timely diagnosis, along with methods with sensitivity and specificity, are urgent for research on the herpes B virus. The lack of a clear understanding of the host invasion and life cycle of the herpes B virus has led to slow progress in the development of effective vaccines and drugs. This review discusses the research progress and problems of the epidemiology of herpes B virus, detection methods and therapy, hoping to inspire further investigation into important factors associated with transmission of herpes B virus in macaques and humans, and arouse the development of effective vaccines or drugs, to promote the establishment of specific pathogen-free (SPF) monkeys and protect humans to effectively avoid herpes B virus infection.